Mō̜radok phūmpanyā thāng watthanatham = Intellectual cultural heritage (Krom Songsœ̄m Watthanatham, Krasūang Watthanatham, 2010)
On the designation of Thailand's intellectual cultural heritage and the designated intellectual cultural heritage items in 2010 and 2009, Thailand.